Association Between the Central Venous Pressure and All-Cause Mortality in Critically Ill Patients with Acute Kidney Injury - Huang A (Dove Medical Press, 2021)
Aifang Huang,1 Lin Liao,2 Ling Pan,1 Liao Pinhu3 1Renal Division, Department of Medicine, First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of China; 2Department of Clinical Laboratory, First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of China; 3Department of Emergency, First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of ChinaCorrespondence: Liao PinhuDepartment of Emergency, First Affiliated Hospital of Guangxi Medical University, Nanning, 530021, Guangxi Zhuang Autonomous Region, People’s Republic of ChinaTel +867712806099Email liaopinhu@163.comPurpose: Elevated central venous pressure (CVP) plays an important role in the occurrence of acute kidney injury (AKI) and it is also independently associated with the prognosis of critically ill patients. However, the effect of CVP on critically ill AKI patients remains unclear. In this study, we analyzed the relationship between CVP and all-cause mortality of critically ill patients with AKI.Patients and Methods: The clinical data of patients in intensive care unit (ICU) were retrieved from the Medical Information Mart for Intensive Care III (MIMIC-III) database and retrospectively analyzed. The all-cause mortality for up to 90 days was the main observed outcome. We used the minimum CVP value obtained during the first 72 hours after ICU admission for our analysis and patients were grouped according to this parameter. Patients were also analyzed after being further divided according to stages 1, 2 and 3 of AKI. Multiple Cox regression and Kaplan–Meier analyses were used to explore the association between CVP measurements and death of ICU patients with AKI.Results: A total of 1986 ICU patients with AKI were studied. A total of 527 (26.5%) patients died by day 90. The high CVP group (patients with ≥ 10 mmHg) had the lowest 90-day survival rate (P =0.001 by log rank test) when according to Kaplan–Meier analysis. By using Cox regression analysis, high CVP was found to be linked to an increase in mortality (CVP ≥ 10 mmHg versus ≤ 5 mmHg, HR, 1.336, 95% CI, 1.064 to 1.677, P trend=0.014). Furthermore, when using in a multivariate Cox regression analysis with CVP as a continuous variable, the higher CVP levels were still an independent risk factor for 90-day all-cause mortality (per 1 mmHg increase, HR, 1.031, 95% CI, 1.013– 1.049, P=0.001). In subgroup analysis, a similar trend was observed in patients with AKI stages 2 and 3.Conclusion: The minimum CVP level during the first 72h after ICU admission was positively associated with mortality in critically ill patients with AKI and this more marked in cases with severe AKI.Keywords: intensive care, kidney disease, 72h CVP value, Kaplan–Meier curve, Cox regression analysis, AKI stage